Treatment of humeral condylar fractures and humeral intracondylar fissures in cats with patellar fracture and dental anomaly syndrome (2020)
The aim of this study is to describe the treatment and outcome of humeral condylar fractures and humeral intracondylar fissures in cats with patellar fracture and dental anomaly syndrome (PADS) and to provide advice on how to manage these cases in practice. Methods: Data were collated on cats with PADS that were reported to have sustained humeral fractures or had fractures or fissures of the humerus identified on radiographs. The details of the fractures were recorded in addition to any treatment and outcome information. Results: Of the 207 cases reported with PADS, 18 cats (8.7%) were found to have humeral condylar fractures, none of which was known to have resulted from significant trauma. Where treatment occurred, it involved the placement of transcondylar positional or lag screws. In some cases additional implants, including supracondylar bone plates and screws or Kirschner wires (K-wires), were used. Follow-up data revealed that only two cats were euthanased owing to the presence of the humeral fractures, with at least eight achieving some degree of recovery of function. Conclusions and relevance: These humeral fractures all have the characteristics of stress insufficiency fractures, being simple isolated fractures that are short oblique, with increased radio-density at the fracture line and occurring following minimal or no trauma. Humeral intracondylar fissures were identified in two cats and it is possible that some of the other fractures may have occurred secondary to pre-existing fissures. To our knowledge, no prior reports exist of fissures in cats that do not meet the criteria for PADS. Surgical repair primarily consisted of the placement of transcondylar lag or positional screws with, in some cases, adjunct implants such as bone plates and screws or K-wires. Though there were insufficient data to determine the prognosis for these fractures in the long term, unlike patellar fractures, many of these fractures will heal if treated appropriately.